Evaluation of local feedstocks for biochar production and potential use of it as soil amendment for lettuce (lactuca sativa.l) production - Atiah, Kofi (University of Cape Coast, 2012)
Agricultural waste can be processed under pyrolysis to generate energy for cooking, resulting in a byproduct called biochar. Biochar has the potential to be used as a soil amendment but this facility has not been explored by researchers. Unpelletized corn cob and oil palm press were subjected to water boiling test, burning duration test, biomass consumption rate, biochar yield, pH of residual water and flame characteristics using Lucia stove. The results generally indicated that corn cob feedstock did better than oil palm press in the parameters assessed. The completely randomized design was used in experiment two to four to assess corn cob biochar effect on growth and yield of lettuce. Six treatments and four replications of biochar were used in a pot trial on an Oxisol. Biochar rates applied were 0 %, 1 %, 2 %, 3 %, 4 % and 5 %. Biochar additions showed significant differences on height and total dry matter but not on number of leaves at maturity (P > 0.05). In experiment three, the biochar was combined with three levels of poultry manure (PM) at 2.5, 5 and 10 t ha-1 with four replications. There were significant increases in height, number of leaves and on total dry matter (P < 0.05). Among the treatments, 3 % (78 t ha-1) biochar with 10 t ha-1 of PM gave superior response on growth and yield of lettuce. In experiment four biochar applied to soil increased pH, available P, total nitrogen, ECEC, exchangeable Mg+2 and K+; reduced exchangeable acidity, compared to the control. The results indicate that the biochar generated may serve as a useful liming material on the acidic Oxisol.
xv,126p,ill.
Keywords: pyrolysis; agricultural waste; biochar; feedstocks; local feedstocks